ChemInform Abstract: Recyclable Palladium Catalyst on Grapheme Oxide for the C—C/C—N Cross‐Coupling Reactions of Heteroaromatic Sulfonates. Issue 50 (December 2015) - Yang, Quanlu; Quan, Zhengjun; Wu, Shang; Du, Baoxin; Wang, Mingming; Li, Peidong; Zhang, Yinpan; Wang, Xicun
Abstract: The catalyst is recyclable and reusable at least 5 times (Suzuki coupling).